Effectiveness of Ethanol Gel and Essential Oil of Kencur Rhizome (Kaempferia galanga L.) base Karbopol against Propionibacterium acnes - Rahayu Samalo; Tri Gunaedi; Dirk Y.P. Runtuboi (Quagga: Jurnal Pendidikan dan Biologi, 2024)
Kencur rhizome (Kaempferia galanga L.) is an aromatic herbal plant as antibacterial and anti-inflammatory. This study aims to determine the physical quality and effectiveness of gel preparations of ethanol extract and essential oil of kencur rhizome based on carbopol inhibiting Propionibacterium acnes bacteria. This study used a Randomized Block Design (RAL) with 2 different treatments of 5 levels each, namely ethanol extract gel treatment and essential oil extract gel with concentrations of 10%, 20%, 30%, 40% and 50%. The results of the gel formulation of extracts and essential oils based on carbopol showed pH, texture, spreadability and adhesiveness according to the quality standards of topical preparations. The antibacterial inhibition of the gel was moderate at 50% extract concentration (11.41 mm); and 50% essential oil (9.04 mm). Positive control treatment inhibited growth by 15.84 mm while negative control showed no response. The extract gel and essential oil of galangal rhizome had a significant effect but were less effective in inhibiting P. acnes bacteria. Adding the maximum concentration of extract and essential oil can optimize acne healing.